Time use surveys and experienced well-being in France and the United States - Flèche, Sarah (OECD Publishing, 2017)
The last decade has seen a sustained surge of interest in measures of subjective well-being on the part of economists and other social scientists. The vast majority of the academic literature on subjective well-being focuses on measures of life evaluation, as does most discussion of how measures of subjective well-being can be applied to policy. However, measures of life evaluation have well-known limitations, and other measures of subjective well-being, including experienced well-being (i.e. people's time use and emotional state over time), can be an important complement to measures of life evaluation. As of 2016, however, few countries have included experienced well-being in their official time use surveys, and there is relatively little understanding of how different methodological approaches to measuring experienced well-being affect the results obtained. This paper presents results using data from the US and the French time use surveys, showing that the different approaches adopted by these two countries have quite different implications for the data collected. Results highlight the sensitivity of experienced well-being measures - particularly the U-index - to the choice of affective states included, and shed light on the differing results found in the literature on how unemployment impacts upon experienced well-being
Keywords: Social Issues/Migration/Health; Economics; France; United States